Notes to Philosophy 167: Class 11 -- Other Developments in Astronomy from 1642 to 1684 -- Part 13. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Flamsteed and the Greenwich Observatory -- Changing Attitudes in Observational Astronomy -- Observational Anomalies: The Speed of Light.; Generally corresponds to the video segment: Class 11, Part 13.